Optical fragment tracking in hypervelocity impact experiments. (February 2019) - Watson, Erkai; Gulde, Max; Kortmann, Lukas; Higashide, Masumi; Schaefer, Frank; Hiermaier, Stefan
Abstract: In-orbit impacts between satellites and space debris lead to varying degrees of fragmentation, ranging anywhere from minor damage to complete breakups. In this paper, we describe an experimental measurement approach for studying fragmentation caused by hypervelocity impact in the laboratory. We investigate impacts on thin aluminum bumper plates with the goal of measuring individual fragment velocities and sizes generated by hypervelocity impact. The experimental setup, commonly used in fluid dynamics for Particle Tracking Velocimetry, consists of using a laser plane and high-speed video camera to track the motion of debris fragments. We describe the fragment tracking algorithm and demonstrate its ability to determine fragment velocity and sizes in specific hypervelocity impact experiments performed at Fraunhofer EMI. The measurement technique enables quantitative data, at an unprecedented level of detail, to be measured from hypervelocity impact fragmentation experiments in the lab, which can be applied to understanding the effects of satellite collisions and improving breakup models. Highlights: Method for instrumenting hypervelocity impact experiment with laser sheet and high-speed camera. Individual debris cloud fragments optically tracked. Important fragment characteristics, such as size, velocity, and mass determined.